AB1211 IMMUNE-RELATED ADVERSE EVENTS IN PATIENTS RECEIVING PD-1/PD-L1 INHIBITORS: PRELIMINARY RESULTS FROM A PROSPECTIVE COHORT STUDY. (2nd June 2020) - Ferrarini, A.; Benfaremo, D.; Rossetti, G.; Morgese, F.; Tonnini, C.; Berardi, R.; Gabrielli, A.; Pomponio, G.
Abstract : Background: Recent introduction of immune checkpoint inhibitors (ICIs) revolutionized oncological guidelines. Immune-related adverse events (IrAEs) may occur in as many as 85% of patients (10% with toxicity grade 3/4), but detailed epidemiology of irAEs is still lacking, mostly because of data collection and analysis vary widely. Objectives: The purpose of our study is to establish a prospective cohort of patients treated with PD-1/PD-L1 inhibitors in order to determine incidence, risk factors and characteristics of irAEs in a real-world setting. Methods: We conducted a prospective cohort study enrolling patients receiving anti-PD-1/PD-L1 agents for the treatment of metastatic or locally advanced non-small cell lung cancer, renal cell carcinoma, squamous cell carcinoma of the head and neck, Hodgkin lymphoma. Detailed recommendations have been implemented for cases fulfilling criteria for suspected irAEs, including procedures for evaluation and diagnosis, specific treatments and rules for drug discontinuation. IrAEs have been defined and graded according to Common Terminology Criteria for Adverse Events vs 5.0. Management strategies have been adapted by a multidisciplinary panel, basing on the oncological guidelines, which represent the current best clinical practice. AEs screening, physical examination, ECG and clinical laboratory evaluation have been performed at baseline visit and follow up (4, 8, 12 weeks). Results: Fifty-two patients have been enrolled from Jan 2019 to Dec 2020. Characteristics are reported in the Table below. Twelve patients developed irAEs (23%), 6 treated with nivolumab, 4 with pembrolizumab, 1 with atezolizumab and 1 with durvalumab. Mild-to-moderate (G1-G2) irAEs were hepatitis, hypothyroidism, III-V-VII cranial nerve palsy, polymyalgia-like syndrome, skin psoriasis and type-1 diabetes mellitus. Severe cases (G3) of bullous dermatitis, Lichen Planus, interstitial pneumonia and myositis occurred. One patient developed three different irAEs. Median time of onset was 4.5 weeks. IrAEs were successfully treated according to established guideline, but 4 patients stopped anti-neoplastic therapy due to irAEs and 11 for disease progression. Five patients died. Conclusion: Cancer patients receiving PD-1/PD-L1 agents are being prospectively followed. Preliminary results confirm that 1/4 patients may develop irAEs. Innovative tools are required in order to manage irAEs, prevent potential relapse and avoid useless interruption of therapy. Further research needs to get insights into pathophysiological mechanisms and risk factors. References: [1]Arnaud-Coffin P. A systematic review of adverse events in randomized trials assessing immune checkpoint inhibitors. Int J Cancer. 2019; Champiat S, Lambotte O, Barreau E, et al. Management of immune checkpoint blockade dysimmune toxicities: a collaborative position paper. Annals of Oncology 27, 2016. Disclosure of Interests: None declared